Learning principles of evolution during a crisis: An exploratory analysis of student barriers one week and one month into the COVID‐19 pandemic. Issue 22 (15th September 2020) - Driessen, Emily; Beatty, Abby; Stokes, Alexis; Wood, Sara; Ballen, Cissy
Abstract: The coronavirus disease (COVID‐19) outbreak forced an emergency transition to online classes across the world with little warning or instruction for faculty and students. The goal of this research was to document how this response impacted undergraduate students studying the principles of evolution in an introductory organismal biology class over time; specifically, how their study habits for exams differed (a) one week and (b) one month after a university's decision to transition to emergency remote instruction. We asked students about the extent to which COVID‐19 impacted their study habits, and we categorized students' responses using open coding. We identified a number of consistent similarities—as well as dramatic differences—in their responses as the time away from campus increased. The report that follows is a summary of the documented barriers and recommendations based on literature concerning crises and equitable practices. Abstract : The goal of this research was to document how the response to COVID‐19 impacted undergraduate students studying the principles of evolution in an introductory organismal biology class over time; specifically, how their study habits for exams differed (a) one week and (b) one month after a university's decision to transition to emergency remote instruction. The report that follows is a summary of the documented barriers and recommendations based on literature concerning crises and equitable practices.